(untitled) (Eureka Journal of Language, Culture & Social Change, 2026)
This article examines the sociolinguistic problems faced by senior high school students in the process of learning a foreign language and ways to overcome them. During the study, the technology of "Situational Pragmatic Simulation" was proposed to develop students’ language skills in a social context. The results show that the formation of sociolinguistic competence is the main factor in reducing the language barrier in students.